The the relationship between personality rights and fundamental and human rights (Revista do Tribunal Regional Federal da 3ª Região, 2022)
This article examines the relation of personality rights to fundamental rights and human rights, a subject that generates a lot of confusion among the legal operators. This is a research that uses descriptive and deductive methodology, fundamentally based on bibliographic, jurisprudential and legislative research. The study begins with the search for the foundation of human rights, a theme that puts jusnaturalism and positivism in opposition. Then, the text systematically examines the distinctions among the personality rights, fundamental rights and human rights, demonstrating that despite many similarities, these rights are not confused. Based on the constitutionalization of civil law, is analyzed the emergence and development of the horizontal effectiveness theory of fundamental rights, which creates a very unique relation with the rights of the personality. Finally, the paper studies in which situations and how the theory of horizontal effectiveness should be applied.
Keywords: Personality rights; fundamental rights; constitutionalization; neoconstitutionalism